In vitro propagation of XXY human Klinefelter spermatogonial stem cells: A step towards new fertility opportunities - Galdon, Guillermo; Deebel, Nicholas A.; Zarandi, Nima Pourhabibi; Teramoto, Darren; Lue, YanHe; Wang, Christina; Swerdloff, Ronald; Pettenati, Mark J.; Kearns, William G.; Howards, Stuart; Kogan, Stanley; Atala, Anthony; et al. (Frontiers in Endocrinology, 2022)
Klinefelter Syndrome (KS) is characterized by a masculine phenotype, supernumerary sex chromosomes (47, XXY), and impaired fertility due to loss of spermatogonial stem cells (SSCs). Early testicular cryopreservation could be an option for future fertility treatments in these patients, including SSCs transplantation or in vitro spermatogenesis. It is critically essential to adapt current in vitro SSCs propagation systems as a fertility option for KS patients. KS human testicular samples (13,15- and 17-year-old non-mosaic KS boys) were donated by patients enrolled in an experimental testicular tissue banking program. Testicular cells were isolated from cryopreserved tissue and propagated in long-term culture for 110 days. Cell-specific gene expression confirmed the presence of all four main cell types found in testes: Spermatogonia, Sertoli, Leydig, and Peritubular cells. A population of ZBTB16+ undifferentiated spermatogonia was identified throughout the culture using digital PCR. Flow cytometric analysis also detected an HLA-/CD9+/CD49f+ population, indicating maintenance of a stem cell subpopulation among the spermatogonial cells. FISH staining for chromosomes X and Y showed most cells containing an XXY karyotype with a smaller number containing either XY or XX. Both XY and XX populations were able to be enriched by magnetic sorting for CD9 as a spermatogonia marker. Molecular karyotyping demonstrated genomic stability of the cultured cells, over time. Finally, single-cell RNAseq analysis confirmed transcription of ID4, TCN2, and NANOS 3 within a population of putative SSCs population. This is the first study showing successful isolation and long-term in vitro propagation of human KS testicular cells. These findings could inform the development of therapeutic fertility options for KS patients, either through in vitro spermatogenesis or transplantation of SSC, in vivo.